Victim and Offender Ratings of Mediations and Restorative Justice Conferences: Findings from a Danish Randomized Controlled Trial - van Mastrigt, Sarah (Victims & offenders, 2025)
This article presents initial survey findings from the first randomized controlled trial to compare two forms of restorative justice. Cases referred to the Danish police’s restorative justice program (konfliktråd) were randomly allocated to either victim-offender mediation (n = 101) or a restorative justice conference (n = 99), and follow-up surveys were sent to victims and offenders 1 and 6 months after all convened meetings. Based on responses from 135 victims and 121 offenders, we explore group differences for four measures capturing participants’ overall assessments of the fairness of their meeting, the extent to which it repaired harm, helped them move on, and was an overall success. Analyses revealed generally positive ratings for all outcomes and both interventions, with some decreases observed over time. For offenders, no significant differences emerged between the experimental conditions for any outcomes, whereas victims assessed mediations significantly more positively than conferences for overall success and harm repair at 6 months. While these findings fail to support our theoretical hypothesis that conferences would be rated more favorably for all outcomes, respondents’ positive assessments of both meeting types generally support the use of both mediation and conferencing methods, offering new insights for future research and practice.